Effectiveness of focus group discussion about violence in children - Erma Wahyu Mashfufa (University of Muhammadiyah Malang, 2018)
According to the Indonesian Child Protection Commission, violence against children is divided into: physical violence, neglect, sexual violence, and emotional violence. The recent rise in cases of child abuse and tending to increase from year to year indicates a weakening of concern and concern for the case. FGD as a method of learning for parents in an effort to increase knowledge and ability to recognize violence prevention in children. This study included experimental quasy research type with pretest-posttest group design. The research variables are FGD and level of knowledge with ordinal data scale. Data presented descriptively in the form of percentage, tabulation of frequency / cross tabulation and analysis with test of wilcoxon Result: Wilcoxon test result got p value (0.000) <α (0.05). Discussion: FGDs on child abuse effectively increase the knowledge of parents. FGD method is the most easily accepted method by parents